First record of the Mouse-colored Tyrannulet, Phaeomyias murina (Spix, 1825) (Aves, Tyrannidae), for Rio Grande do Sul, Brazil - Mauricio da Silveira Pereira (Check List, 2017)
I report here the first record of the Mouse-colored Tyrannulet, Phaeomyias murina, for the state of Rio Grande do Sul, southern Brazil. On 12 December 2013, one individual was photographed and tape-recorded in a gallery forest at Dezesseis de Novembro, in the northwest sector of the state. This record may be linked to the species’ migratory habits in the southern part of its distribution, as it regularly occurs as a summer resident in adjacent areas of Argentina and Paraguay.